Eastern Roman mounted archers and extraordinary medico-surgical interventions at Paliokastro in Thasos Island during the ProtoByzantine period : the historical and medical history records and the archaeo-anthropological evidence - Agelarakis, Anagnostis P., 1956- (Access archaeology., 2020)
Procopius' 'History of the Wars', and the 'Strategikon' offer important aspects of Eastern Roman military tactical changes adopted against their enemies that brought the mounted archer-lancer to domineer in the synthesis of the army, along with concise descriptions of their training, panoply, and effectiveness in the battlefield during the later ProtoByzantine period. Yet, evidence in the archaeo-anthropological records of these highly specialized military members has remained elusive.0A recent archaeological discovery at the strategically positioned, upland, site of Paliokastro in Thasos island, Greece, and the subsequent study of the human skeletal remains interred in four monumental funerary contexts, in a dedicated 'naiskos' building, provide for the first time through the archaeological record of the region a unique insight of the mounted archers and their female kin during the turbulent ProtoByzantine period. The interdisciplinary study of the anthropological materials focusing on skeletal developmental, acquired skeleto-muscular manifestations and skeleto-anatomical changes recovered valuable evidentiary data on aspects of their in vivo long-term training and preparation, traumatisms and pathologies along with extraordinary traces of cranial and infra-cranial surgical interventions and medical regimens by the hands of a most experienced surgeon.0In conjunction with the archaeological and anthropological evidence, historical and medical history records are integrated aiming toward a nexus with the human dynamics that transpired at Paliokastro within the context of the catastrophic consequences of the 'barbarian' invasions in the Aegean Thraco-Macedonia, and the ravages afforded by the Justinian plague during the later component of the ProtoByzantine period.